2019
DOI: 10.1002/cam4.2019
|View full text |Cite
|
Sign up to set email alerts
|

Chlorotoxin targets ERα/VASP signaling pathway to combat breast cancer

Abstract: Breast cancer is one of the most common malignant tumors among women worldwide. About 70‐75% of primary breast cancers belong to estrogen receptor (ER)‐positive breast cancer. In the development of ER‐positive breast cancer, abnormal activation of the ERα pathway plays an important role and is also a key point leading to the failure of clinical endocrine therapy. In this study, we found that the small molecule peptide chlorotoxin (CTX) can significantly inhibit the proliferation, migration and invasion of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…They also inhibit MMP activity in breast and colorectal cancers, thereby reducing the motility and invasion of tumor cells, and induce apoptosis by decreasing the expression of antiapoptotic proteins and increasing that of proapoptotic proteins [ 80 ]. In addition, chlorotoxin derived from scorpion toxin inhibits the expression of ERα in breast cancer cells by inhibiting the ERα signaling pathway through direct binding to ERα, thus changing the protein secondary structure of its LBD domain [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also inhibit MMP activity in breast and colorectal cancers, thereby reducing the motility and invasion of tumor cells, and induce apoptosis by decreasing the expression of antiapoptotic proteins and increasing that of proapoptotic proteins [ 80 ]. In addition, chlorotoxin derived from scorpion toxin inhibits the expression of ERα in breast cancer cells by inhibiting the ERα signaling pathway through direct binding to ERα, thus changing the protein secondary structure of its LBD domain [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…A synthetic CTX peptide labeled with 131 I (commercial name 131 I-TM-601) has already undergone early-phase clinical trials and received Food and Drug Administration (FDA) approval for a phase III trial in patients with newly diagnosed gliomas [ 114 ]. In addition to its high selectivity for targeting and binding of GB tumors, CTX has been shown to bind to a broad-spectrum of cancer cells including NB, medulloblastoma, breast cancer, ovarian cancer, prostate cancer, sarcoma, intestinal cancer, lung cancer and pancreatic cancer [ 45 , 48 , 49 , 50 , 51 , 53 , 54 , 62 , 110 , 115 , 116 ]. For peptides to be considered useful in therapeutics, they should normally possess the following characteristics: a small molecular size, clear activity on ion channels, and contain at least three disulfide bonds [ 60 ].…”
Section: Chlorotoxin (Ctx): a Promising Natural Targeting Peptide For...mentioning
confidence: 99%
“…The exact mechanisms by which CTX targeting occurs are not completely understood but potential primary cell surface targets have been identified over the years ( Figure 2 ). Some studies have shown that CTX is an effective blocker of small conductance epithelial chloride channels [ 118 , 119 ] and mainly binds to overexpressed cancer cell surface receptors involved in the progression of tumors such as ClC-3 (chloride channel-3) in GB cells [ 37 , 38 , 110 , 119 , 120 , 121 , 122 , 123 , 124 ] which forms a protein complex with matrix metalloprotease-2 receptor (MMP-2) [ 48 , 49 , 50 , 116 , 125 , 126 ]; annexin A2 which is present in various cell lines [ 51 , 52 ] and has since been shown to be a potential target of CTX, and more recently estrogen receptor alpha (ERα) [ 53 ] and the Neuropilin-1 (NRP-1) [ 54 , 55 ] which is a vascular endothelial growth factor receptor responsible for tumor uptake. These molecules provide alternative methods for CTX targeting tumors in cancer diagnosis and therapy.…”
Section: Chlorotoxin (Ctx): a Promising Natural Targeting Peptide For...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on reptile-derived venom has also been conducted, and several effects on cancer cells have been demonstrated. Lectin purified from Macrovipera lebetina, BnSP-6 and Lys-49 phospholipase A2 (PLA2) purified from Bothrops pauloensis, NN-3 purified from Naja naja oxiana, and chlorotoxin purified from Leiurus quinquestriatus were analyzed to determine their structure, amino acid sequence and anticancer effect against MDA-MB-231 cells [90][91][92][93]. Additionally, macrovipecetin, a C-type lectin from Macrovipera lebetina, suppressed the migration, invasion and proliferation of the human melanoma cell line SK-MEL-28 [94].…”
Section: Venommentioning
confidence: 99%